'Imposed consociationalism': external intervention and power sharing in Bosnia and Herzegovina. (2nd January 2017) - Merdzanovic, Adis
Abstract: This paper analyses the interplay between international intervention and the functioning of the domestic political system in post-war Bosnia and Herzegovina. The Dayton Peace Agreement set up a formally sovereign consociational power sharing system in which international actors nevertheless kept intervening. By doing so, they changed the character of the system and, more importantly, the incentive structures for political action. The result is an 'imposed consociational democracy' which promotes extremist rather than accommodative behaviour. Relying on interviews with former High Representatives and domestic political decision-makers, as well as a longitudinal analysis of newspaper coverage, this paper seeks to outline the evolution of the 'imposed consociational' system in Bosnia and Herzegovina and its contribution to the challenges the country faces today.